Investigation of routine venous augmentation in deep inferior epigastric artery perforator flap and intraoperative decision pathway - Meyer, Anne; Bird, Cole; Nazir, Niaman; Collins, Meredith; Lai, Eric C; Farmer, Rebecca; Butterworth, James; Holding, Julie (Journal of Reconstructive Microsurgery)
Background: Data supporting use of prophylactic venous augmentation in the deep inferior epigastric perforator flap (DIEP) is limited. This study aims to assess the outcomes of single vein DIEP flaps compared to those with venous augmentation and present an intraoperative decision pathway. Methods: A retrospective chart review was performed on patients who underwent DIEP flap reconstruction at a single institution from 2009 to 2023. Statistical analysis was performed and p-values less than 0.05 were considered statistically significant. Results: A total of 1,099 patients had DIEP flap breast reconstruction resulting in 1,745 flaps. Two or more veins were utilized in 32.4% while 67.6% had a single venous anastomosis. Prophylactic augmentation was documented for 24.5% of flaps. The rate of return to operating room was 5.8% with no significant difference found in the rate of return for all causes (p=0.14) and suspected venous compromise (p=0.95). Suspected venous compromise was documented in 41flaps (2.3%), with no significant difference between the single vein and prophylactic vein group (p=0.95). There was no difference in rates of early (p=0.10) or late flap loss (p=0.15). Difference in operative duration was increased for flaps with prophylactic venous anastomoses (559.4 +/- 127.8 minutes versus 505.6 +/- 130.8 minutes) (p<0.001). Conclusions: This study demonstrates no significant difference in post operative complications as well as demonstrating prophylactic multi-vein anastomosis was associated with significantly longer operative times. With the use of an intraoperative decision pathway, one can determine which flaps will benefit from additional venous outflow and avoid unnecessary routine augmentation without benefit. Keywords: Diep inferior epigastric artery perforator (DIEP) flap, Breast reconstruction, Prophylactic venous augmentation, Flap outcomes, Intraoperative decision pathway